Better pictures on the radio - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
workshop was organised in Suva, Fiji, from 6 to 16 April 1999 by CTA and IRETA, with a course consultant from Wrenmedia